Thermosensitive hydrogels to deliver reactive species generated by cold atmospheric plasma: a case study with methylcellulose. (9th June 2022) - Solé-Martí, Xavi; Vilella, Tània; Labay, Cédric; Tampieri, Francesco; Ginebra, Maria-Pau; Canal, Cristina
Abstract : Hydrogels have been recently proposed as suitable materials to generate reactive oxygen and nitrogen species (RONS) upon gas-plasma treatment, and postulated as promising alternatives to conventional cancer therapies. Abstract : Hydrogels have been recently proposed as suitable materials to generate reactive oxygen and nitrogen species (RONS) upon gas-plasma treatment, and postulated as promising alternatives to conventional cancer therapies. Acting as delivery vehicles that allow a controlled release of RONS to the diseased site, plasma-treated hydrogels can overcome some of the limitations presented by plasma-treated liquids in in vivo therapies. In this work, we optimized the composition of a methylcellulose (MC) hydrogel to confer it with the ability to form a gel at physiological temperatures while remaining in the liquid phase at room temperature to allow gas-plasma treatment with suitable formation of plasma-generated RONS. MC hydrogels demonstrated the capacity for generation, prolonged storage and release of RONS. This release induced cytotoxic effects on the osteosarcoma cancer cell line MG-63, reducing its cell viability in a dose-response manner. These promising results postulate plasma-treated thermosensitive hydrogels as good candidates to provide local anticancer therapies.